2006
DOI: 10.1002/ejic.200600242
|View full text |Cite
|
Sign up to set email alerts
|

Methoxyphenyl‐Functionalized Diiron Azadithiolates as Models for the Active Site of Fe‐Only Hydrogenases: Synthesis, Structures, and Biomimetic H2 Evolution

Abstract: A series of methoxyphenyl-functionalized diiron azadithiolate (ADT) complexes,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
53
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 37 publications
5
53
0
Order By: Relevance
“…On the other hand, the reduction shifts are smaller than those observed for complex 6 and other reported phosphane-substituted diiron complexes. [19,20,30,42] Within the series of 2, 4, and 6, we can see that the reduction potentials gradually shift to more positive potentials with displacement of the phenyl ring by the pyrrol-1-yl group, consistent with the change trends of the IR ν CO bands.…”
Section: Electrochemistry Of Complexes 2-5supporting
confidence: 78%
See 4 more Smart Citations
“…On the other hand, the reduction shifts are smaller than those observed for complex 6 and other reported phosphane-substituted diiron complexes. [19,20,30,42] Within the series of 2, 4, and 6, we can see that the reduction potentials gradually shift to more positive potentials with displacement of the phenyl ring by the pyrrol-1-yl group, consistent with the change trends of the IR ν CO bands.…”
Section: Electrochemistry Of Complexes 2-5supporting
confidence: 78%
“…It has been demonstrated that complexes 2 and 3 display two irreversible oxidation peaks, whereas 4 and 5 show one irreversible oxidation peak. In publications, those reported for ADT-, PDT-, and ODT-bridged (ODT = oxadithiolato) analogs, [19][20][21]30,41,42] In all cases discussed in this paper, it is noticeable that the 1st oxidation for complexes 2-5 exhibits a current intensity ca. twice that of the corresponding 1st reduction event, which was confirmed as a one-electron process by bulk electrolysis (vide infra).…”
Section: Electrochemistry Of Complexes 2-5mentioning
confidence: 81%
See 3 more Smart Citations